Najstarsze północnoamerykańskie artykuły wojskowe - Łopatecki, Karol (Czasopismo Prawno-Historyczne, 2018)
This paper analyses from historical and legal points of view, military articles enacted for militias stationed in the colonies of Virginia, Massachusetts, Connecticut and Maryland. All the studied articles were drafted by selecting legal norms from model military articles and introducing minor stylistic changes. Colonists from Virginia took advantage of Sweden’s Gustav II Adolph’s articles of 1621, those from Massachusetts – articles drafted for the Parliamentarian Army by Robert Devereux in 1642 while in Maryland, Prince Rupert’s Articles of 1672 served as a model. The example of Connecticut shows that once a version of regulations for militias had been published, it was eagerly copied by neighbouring colonies. Curiously enough – an observation that has not been made in the literature so far – the Swedish military regulations of Gustav II Adolph were made use of outside Europe. This only bears out the claim that military expertise fl owed freely in the times of ‘military revolutions’. A new type of source concerning military law, namely militia articles, needs to be distinguished; one marked by conciseness, for it only laid down absolutely necessary regulations that could be enforced in ad hoc formed militias.